Rentannya UMKM Menghadapi Pandemi Covid-19 dan Kaitannya dengan Kualitas Sumber Daya Manusia - Daniel Collyn; Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2026)
The Covid-19 pandemic has dealt a hard blow to various economic sectors in Indonesia, including MSMEs. The results of the Katadata Insight Center survey, as many as 56.8 percent of MSMEs are in bad condition, while MSMEs are in good condition only 14.1 percent. MSMEs that experienced the negative impact of the pandemic reached 82.9 percent, only 5.9 percent experienced a positive impact. The vulnerability of MSMEs in facing the Covid-19 pandemic is mainly due to the lack of ability of MSME actors to master technology and formulate business strategies. As a result, the utilization of technology by SMEs is very low. This condition is evidence that the quality of human resources for SMEs in Indonesia is still low. There are still many MSMEs that have not maximized the e-commerce platform as a medium to market their products. This is motivated by the low awareness of MSME actors about the importance of technology, and also the low ability of human resources in mastering technology. In fact, MSMEs during a pandemic can survive and grow when they have human resources who master digital technology. The study analyzed human resource problems in MSMEs during the Covid-19 pandemic in terms of the previous literature. In this study, activities for collecting, managing and analyzing data taken from related written literature will be carried out so that the description of human resource problems in MSMEs during the Covid-19 pandemic is known clearly.